The risk and performance of ethically compliant investment - Norhidayah, Abu Bakar; Norizan, Remli; Juliana, Arifin (Penerbit Universiti Sultan Zainal Abidin, 2020)
This paper presents a discussion of prior literature on the risk and performance of ethically compliant equity. This review of literature provides an organised evaluation of the available studies in ethical investment. In particular, this paper presents surveys of literature concerning shariah-compliant equity and socially responsible investments. The discussion of the literature synthesises the information in the respective studies into a summary. Each subsection provides an analysis of the information gathered by first providing an overview of the current empirical studies and, second, identifying gaps and showing the limitation of theoretical views in the existing studies. Discussion in previous literature emphases only one type of ethical investment, however, this paper, on the other hand, covers both the religious and social perspectives of ethics, which provide a more comprehensive view of ethics. The paper finds out that studies on the risk and performance of ethically compliant investment report mixed results. This is due to the disparities in the research methodological approach. However, it is almost unanimous that ethical funds demonstrate higher stability (lower risk) during the financial crisis and tend to outperform the conventional funds during this state of financial uncertainty. Future studies can conduct more firm-level analysis and integrates both screening criteria (shariah and socially responsible screening) to reconcile the results.